The interplay between kisspeptin and endocannabinoid systems modulates male hypothalamic and gonadic control of reproduction in vivo - Marino, Marianna; D’Auria, Raffaella; Mele, Elena; Pastorino, Grazia Maria Giovanna; Di Pietro, Paola; D’Angelo, Stefania; Della Rocca, Natalia; Operto, Francesca Felicia; Vecchione, Carmine; Fasano, Silvia; Pierantoni, Riccardo; Viggiano, Andrea; et al. (Frontiers in Endocrinology, 2023)
Introduction Male reproduction is under the control of the hypothalamus–pituitary–gonadal (HPG) axis. The endocannabinoid system (ECS) and the kisspeptin system (KS) are two major signaling systems in the central and peripheral control of reproduction, but their possible interaction has been poorly investigated in mammals. This manuscript analyzes their possible reciprocal modulation in the control of the HPG axis. Materials and methods Adolescent male rats were treated with kisspeptin-10 (Kp10) and endocannabinoid anandamide (AEA), the latter alone or in combination with the type 1 cannabinoid receptor (CB1) antagonist rimonabant (SR141716A). The hypothalamic KS system and GnRH expression, circulating sex steroids and kisspeptin (Kiss1) levels, and intratesticular KS and ECS were evaluated by immunohistochemical and molecular methods. Non-coding RNAs (i.e., miR145-5p, miR-132-3p, let7a-5p, let7b-5p) were also considered. Results Circulating hormonal values were not significantly affected by Kp10 or AEA; in the hypothalamus, Kp10 significantly increased GnRH mRNA and aromatase Cyp19, Kiss1, and Kiss1 receptor (Kiss1R) proteins. By contrast, AEA treatment affected the hypothalamic KS at the protein levels, with opposite effects on the ligand and receptor, and SR141716A was capable of attenuating the AEA effects. Among the considered non-coding RNA, only the expression of miR145-5p was positively affected by AEA but not by Kp10 treatment. Localization of Kiss1+/Kiss1R+ neurons in the arcuate nucleus revealed an increase of Kiss1R-expressing neurons in Kp10- and AEA-treated animals associated with enlargement of the lateral ventricles in Kp10-treated animals. In the brain and testis, the selected non-coding RNA was differently modulated by Kp10 or AEA. Lastly, in the testis, AEA treatment affected the KS at the protein levels, whereas Kp10 affected the intragonadal levels of CB1 and FAAH, the main modulator of the AEA tone. Changes in pubertal transition-related miRNAs and the intratesticular distribution of Kiss1, Kiss1R, CB1, and CB2 following KP and AEA treatment corroborate the KS-ECS crosstalk also showing that the CB1 receptor is involved in this interplay. Conclusion For the first time in mammals, we report the modulation of the KS in both the hypothalamus and testis by AEA and revealed the KP-dependent modulation of CB1 and FAAH in the testis. KP involvement in the progression of spermatogenesis is also suggested.